2017
DOI: 10.1111/emr.12243
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of woody species across 26 years of revegetation on a Queensland coal mine

Abstract: Summary The establishment success of woody plant species at 56 revegetation sites, four to 26 years old, across the Meandu open‐cut coal mine in south‐east Queensland was assessed. The revegetation process involved returning stockpiled topsoil, deep ripping and mechanical sowing of a mix of native seeds. Blakes Wattle (Acacia blakei) and less often Black Wattle (A. leiocalyx), both primarily derived from respread topsoil seed, dominate the vegetation canopy at 59% and 20% of revegetation sites, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Our results suggest that OTUs associated with arbuscular mycorrhizas played an important role in the early stages of site rehabilitation, when grass cover and seedlings of naturally regenerating Acacia species (Neldner & Ngugi ) were predominant and before the dominance of woody vegetation and tree canopy closure. The dominance then shifted to ectomycorrhizas in later stages of rehabilitation, correlating with the establishment of partner tree species on the sites.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our results suggest that OTUs associated with arbuscular mycorrhizas played an important role in the early stages of site rehabilitation, when grass cover and seedlings of naturally regenerating Acacia species (Neldner & Ngugi ) were predominant and before the dominance of woody vegetation and tree canopy closure. The dominance then shifted to ectomycorrhizas in later stages of rehabilitation, correlating with the establishment of partner tree species on the sites.…”
Section: Discussionmentioning
confidence: 82%
“…An average of 24 species of trees and shrubs, and five species of herbs, were sown in replaced topsoil at each site at a rate of approximately 8 kg/ha at establishment (Neldner & Ngugi ). An average of 15 tree species were present at year one, but by 20 years only a maximum of six species survived.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, in order to reduce the net loss of biodiversity and ecosystem function and improve environmental quality after the end of mining operations, the law stipulates that the environmental rehabilitation of the mining area should be as close as possible to its pre-disturbance level (Gastauer et al, 2019). In recent years, a battery of methods have been adopted to restore the service functions of destroyed ecosystems after magnesite mining, of which phytoremediation, as an environmentally friendly and cost-effective method (Ahirwal & Maiti, 2018;Kaur et al, 2019;Neldner & Ngugi, 2017), has been generally used in the reclamation for tailings (Deng, Bai, Zhou, Zhu, & Yin, 2020;Li, Chen, & Wen, 2015;Wu et al, 2018;Zhou et al, 2015). Soil quality is an important component of the ecosystems restoration, providing physical, chemical, and biological supports for plant regeneration and establishment (Zhang & Chu, 2013).…”
mentioning
confidence: 99%
“…In order for revegetated sites to become self‐sustaining, it is not only pollination and seed set that need to occur, but also regeneration (Godefroid et al ). In the Monarto Woodlands, eucalypts have been flowering and setting fruit for at least 20 years, but recruitment is rare (Paton et al, personal observation), and a lack of recruitment has also been observed in other revegetated systems (Schneemann & McElhinny ; Nelder & Ngugi ). While manipulating planting arrangements can have positive benefits for reproductive output, it will only be worthwhile if recruitment failure in these systems is also addressed.…”
Section: Discussionmentioning
confidence: 99%